Exportación de carne de cuy a las principales ciudades de China - Andrango Villarroel, Nancy Piedad (2008)
The development proposal is indicated totally viable since the results obtained in the financial analysis and long-term projections, cast figures of recoverable investment during the second year of activity, and the level of profitability is higher than other businesses . Without neglecting the profit generated by a business like this, new jobs and improving the quality of life of those engaged in this activity, which mostly belong to the lower class are also created, and also gives a contribution to economic development.